1985
DOI: 10.2307/2388214
|View full text |Cite
|
Sign up to set email alerts
|

Tree Mortality in Mangrove Forests

Abstract: Twenty-eight worldwide reports of massive mangrove tree mortalities are reviewed. Massive mortality is defined as tree mortalities that occur in response to rapid environmental change and affect all size dasses. Massive mortality occurs in addition to normal tree mortality. Normal tree mortality was described using structural data from 114 mangrove stands. This mortality is density dependent, follows orderly time dependent patterns dictated by stand maturation (related to average tree diameter), and usually oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
120
0
17

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(146 citation statements)
references
References 24 publications
9
120
0
17
Order By: Relevance
“…The growth of mangrove in four distinct zones throughout the bay and their development has presumably been controlled in the past by the time when they established themselves and environmental and biotic variables. Important environmental factors potentially controlling distribution and growth are tidal inundation, soil pore water salinity, sediment stability and type and fresh water input as discussed by several authors (Rabinowitz, 1978a,b,c;Jiménez et al, 1985;Smith, 1987a,b;Cardona and Botero, 1998;Jiménez and Sauter, 1991;Clough, 1992;Smith, 1992;Ellison and Farnsworth, 1993;Duke et al, 1998;Elster, 2000). Additionally the importance of predation on propagules and seedlings has been found to be important in establishment of mangrove.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of mangrove in four distinct zones throughout the bay and their development has presumably been controlled in the past by the time when they established themselves and environmental and biotic variables. Important environmental factors potentially controlling distribution and growth are tidal inundation, soil pore water salinity, sediment stability and type and fresh water input as discussed by several authors (Rabinowitz, 1978a,b,c;Jiménez et al, 1985;Smith, 1987a,b;Cardona and Botero, 1998;Jiménez and Sauter, 1991;Clough, 1992;Smith, 1992;Ellison and Farnsworth, 1993;Duke et al, 1998;Elster, 2000). Additionally the importance of predation on propagules and seedlings has been found to be important in establishment of mangrove.…”
Section: Discussionmentioning
confidence: 99%
“…The dominance of studies in mature mangrove forests has resulted in a lack of field data on mangrove stand development from colonisation, through to early development and maturity (sensu Jiménez et al, 1985), and the effects of disturbance during this process. The study of spatio-temporal changes in mangrove stand extent, structure and composition has recently been defined by Dahdouh-Guebas and Koedam (2002) as mangrove vegetation structure dynamics.…”
mentioning
confidence: 99%
“…If inundation is sustained, low oxygen conditions occur and mortalities follow. This is thought to have been the cause of widespread mortality of Avicennia germinans stands in Puerto Rico recorded by Jimenez et al (1985), following permanent flooding caused by adjacent dredging. Lahmann (1988) found that rates of litterfall in an impounded mangrove forest in Florida were reduced relative to natural fringe forest during flooded months.…”
Section: Increased Salinitymentioning
confidence: 99%
“…Mass of N decreased slowly during most of the experiment and was -80% of the original after 2.3 yr. The C : N ratio of sticks also showed ( Jimenez et al 1985). Secondly, prop roots were assumed to have the same decay rates as trunks.…”
mentioning
confidence: 99%